No earls allowed ebook - Galen, Shana (The Survivors, 2018)
It is a truth universally acknowledged that a lady can do anything a man can do: backwards and in high-heeled dancing slippers. Lady Juliana, daughter of the Earl of St. Maur, needs all the help she can get. She's running a ramshackle orphanage, London's worst slumlord has illicit designs on her, and her father has suddenly become determined to marry her off. Enter Major Neil Wraxall, bastard son of the Marquess of Kensington, sent to assist Lady Juliana in any way he can. Lucky for her, he's handy with repairs, knows how to keep her and the orphans safe, and is a natural leader of men. Unfortunately for both of them, the scandal that ensues from their mutual attraction is going to lead them a merry dance... The Survivors Series: Third Son's a Charm (Book 1) No Earls Allowed (Book 2) An Affair With a Spare (Book 3) Praise for Third Son's a Charm: "Shana Galen's deliciously brooding hero and delightfully quirky heroine turn this tale of adventure into an endearing love story that kept me up all hours reading....Wonderful!" —Sabrina Jeffries, New York Times bestselling author "Shana Galen delivers again!...A sharp, poignant battle of wills between a wonderful wounded hero and the only heroine brave enough to get past his defenses. Don't miss it!" —Eileen Dreyer, New York Times bestselling author "Shana Galen charms readers with poignant and unforgettable characters, humor, and a passionate page-turning tale that's impossible to put down... Galen is an amazing talent and never disappoints." —Lorraine Heath, New York Times and USA Today bestselling author